Sex Differences in Coagulation and Fibrinolysis in Subjects with Coronary Artery Disease - Ossei-Gerning, Nicholas; Wilson, Ian J.; Grant, Peter J. (Thrombosis and Haemostasis, 1998)
Women with coronary artery disease (CAD) have a prognosis at least as bad and possibly worse than men. Differences in classical risk factors do not fully account for these findings and there is evidence that circulating levels of haemostatic factors may predict CAD risk. In this study sex differences in haemostatic risk factors were examined in relation to coronary stenosis.609 (420 men, 69%) subjects admitted for coronary angiography for suspected CAD were recruited. Levels of Factor VII:C (FVII:C), fibrinogen, plasminogen activator inhibitor-1 (PAI-1) and von Willebrand factor (vWF) were estimated in 296 subjects from one centre. Of these, women (n = 107) had higher levels of FVII:C (134% vs 117%, p <0.0005), and fibrinogen (3.4 g/l vs 3.2 g/l p = 0.01) than men (n = 189) and these differences remained after adjusting for other covariates. In subjects with angiographically significant atheroma these differences in haemostatic factors (n = 50 for women vs n = 147 for men) were exaggerated, (FVII:C 139% vs 117, p <0.0001, fibrinogen 3.7 g/l vs 3.3 g/l p = 0.003), PAI-1 (26.2 ng/ml vs 19.7 ng/ml, p = 0.02) with a trend towards higher levels of vWF in the women. Women with significant atheroma at angiography (n = 50) had higher levels of PAI-1 (25.0 ng/ml vs 13.4 ng/ml p <0.0001) and vWF (1.25 IU/ml vs 1.06 IU/ml, p = 0.02) and a trend towards higher levels of both fibrinogen and FVII:C than women with normal or in significant coronary vessel disease (n = 57).Elevated circulating levels of PAI-1, vWF, fibrinogen and FVII:C in women with angiographically proven CAD may contribute to an adverse cardiovascular risk factor profile and the poorer prognosis in females than male patients with proven coronary artery disease.